The shortest history of economics - Leigh, Andrew 1972- (Old Street Publishing, 2024)
This small book tells a big story. From ancient times to the modern world, The Shortest History of Economics unearths the hidden economic forces behind war, innovation and social transformation. It traces how capitalism and the market system emerged, and introduces the key ideas and people who shaped the discipline of economics
Keywords: Economics / History; Économie politique - Histoire